New Intracellular Peptide Derived from Hemoglobin Alpha Chain Induces Glucose Uptake and Reduces Blood Glycemia - Renée N. O. Silva; Ricardo P. Llanos; Rosangela A. S. Eichler; Thiago B. Oliveira; Fábio C. Gozzo; William T. Festuccia; Emer S. Ferro (MDPI AG, 2021)
Intracellular peptides were shown to derive from proteasomal degradation of proteins from mammalian and yeast cells, being suggested to play distinctive roles both inside and outside these cells. Here, the role of intracellular peptides previously identified from skeletal muscle and adipose tissues of C57BL6/N wild type (WT) and neurolysin knockout mice were investigated. In differentiated C2C12 mouse skeletal muscle cells, some of these intracellular peptides like insulin activated the expression of several genes related to muscle contraction and gluconeogenesis. One of these peptides, LASVSTVLTSKYR (Ric4; 600 µg/kg), administrated either intraperitoneally or orally in WT mice, decreased glycemia. Neither insulin (10 nM) nor Ric4 (100 µM) induced glucose uptake in adipose tissue explants obtained from conditional knockout mice depleted of insulin receptor. Ric4 (100 µM) similarly to insulin (100 nM) induced Glut4 translocation to the plasma membrane of C2C12 differentiated cells, and increased GLUT4 mRNA levels in epididymal adipose tissue of WT mice. Ric4 (100 µM) increased both Erk and Akt phosphorylation in C2C12, as well as in epididymal adipose tissue from WT mice; Erk, but not Akt phosphorylation was activated by Ric4 in tibial skeletal muscle from WT mice. Ric4 is rapidly degraded in vitro by WT liver and kidney crude extracts, such a response that is largely reduced by structural modifications such as N-terminal acetylation, C-terminal amidation, and substitution of Leu8 for DLeu8 (Ac-LASVSTV[DLeu]TSKYR-NH2; Ric4-16). Ric4-16, among several Ric4 derivatives, efficiently induced glucose uptake in differentiated C2C12 cells. Among six Ric4-derivatives evaluated in vivo, Ac-LASVSTVLTSKYR-NH2 (Ric4-2; 600 µg/kg) and Ac-LASVSTV[DLeu]TSKYR (Ric4-15; 600 µg/kg) administrated orally efficiently reduced glycemia in a glucose tolerance test in WT mice. The potential clinical application of Ric4 and Ric4-derivatives deserves further attention.